What is the Ethical Impact of Gender Non-Conforming Names?. (2nd November 2021) - Johnson, Richard Greggory; Renderos, Hugo; Gessese, Samrawit; Kuboyama, Alan; Liu, Elizabeth
Abstract : Names? What is in a name? This article endeavors to investigate what is in a name. Names are an important part of an individual's identity. Names, depending on one's culture, defines and identifies an individual. How an individual obtains a name, who names the individual, be it the father or mother of a newborn, or even grandparents, has a lifetime impact on the named individual. There are implications when naming a newborn at birth because the named individual may in the future be transgender. This situation brings negative consequences for any transgender when assigned a name usually associated with a gender. This article conducts a systematic database search for the evaluation of ethical impact on gender non-conforming names.